Psychological Type Profile and Work-Related Psychological Health of Clergy Serving in the Diocese of Chester - Francis, Leslie J. (Practical theology, 2015)
This study examines the psychological type profile and work-related psychological health of ninety-nine clergy serving the Diocese of Chester alongside normative data for the Church of England published in previous studies. The data demonstrated that these clergy share the general psychological type profile of Church of England clergy, with preferences for introversion (60%), intuition (55%), feeling (57%), and judging (76%). Compared with the normative data they show slightly better work related psychological health, with lower levels of emotional exhaustion in ministry and higher levels of satisfaction in ministry. The relevance of such profiling is discussed for the wider Church.